2007
DOI: 10.1002/ijc.23265
|View full text |Cite
|
Sign up to set email alerts
|

Familial clustering of cancer at human papillomavirus‐associated sites according to the Swedish Family‐Cancer Database

Abstract: Familial aggregation of cervical cancer has been demonstrated previously, however aggregation of other human papillomavirus‐associated anogenital, upper aerodigestive tract and skin cancers has not been fully characterized. The Swedish Family‐Cancer Database, which contains reliable data on cancer incidence and nuclear family linkages for all residents of Sweden between 1958 and 2004, was used to calculate standardized incidence ratios (SIR) and 95% confidence intervals for offspring site‐specific cancer risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…However, more cases of adenocarcinoma were registered in their series, 17% [26]. According to studies, cervical squamous cell carcinoma risk is 74% -80% higher in women with a first-degree relative with cervical squamous cell carcinoma, compared to the general population [27]. Cervical adenocarcinoma risk is 39% -69% higher in women with a first-degree relative with cervical squamous cell carcinoma, compared to the general population, a number of studies showed [27].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, more cases of adenocarcinoma were registered in their series, 17% [26]. According to studies, cervical squamous cell carcinoma risk is 74% -80% higher in women with a first-degree relative with cervical squamous cell carcinoma, compared to the general population [27]. Cervical adenocarcinoma risk is 39% -69% higher in women with a first-degree relative with cervical squamous cell carcinoma, compared to the general population, a number of studies showed [27].…”
Section: Discussionmentioning
confidence: 98%
“…According to studies, cervical squamous cell carcinoma risk is 74% -80% higher in women with a first-degree relative with cervical squamous cell carcinoma, compared to the general population [27]. Cervical adenocarcinoma risk is 39% -69% higher in women with a first-degree relative with cervical squamous cell carcinoma, compared to the general population, a number of studies showed [27]. Cervical squamous cell risk is 15% higher in women who have had 1 full-term pregnancy than in those who have never had; the risk increases with the number of fullterm pregnancies [28].…”
Section: Discussionmentioning
confidence: 99%
“…The difference between these two approaches is that somatic variants provide insight into the pathways involved in disease causation, subtypes or progression, offering potential drug targets or prognosis information, whereas inherited variants provide information regarding who is at greater risk of developing the disease, as well as informing disease aetiology. The heritability of VSCC has not been quantified, although familial clustering has been reported in Sweden and Australia, which is suggestive of a role for inherited genetic risk factors . It is also notable that heritability has been estimated to explain 27% of the variability in risk of cervical cancer, with inherited genetic variants thought to influence susceptibility to and persistence of HPV infection, and time to development of cancer …”
Section: Geneticsmentioning
confidence: 99%
“…Host genetic factors may play a role in cervical carcinogenesis and are believed to influence persistence of HPV infection and perhaps progression to cervical cancer (Hemminki et al, 1999;Czene et al, 2002;Hildesheim and Wang, 2002;Carrington et al, 2005;Hemminki and Chen, 2006;Hussain et al, 2008). The role of nongenetic cofactors in persistence and progression has been well studied, but there are very few studies on the role of host genetic factors in the pathogenesis of cervical cancer.…”
Section: Introductionmentioning
confidence: 98%